Nursery subsidy as an instrument of legislative and expenditure independence of a commune self-government - Anna Ostrowska (Prawo Budżetowe Państwa i Samorządu)
The Act on a care of children up to 3 years of age which has been passed in 2011 introduced revolutionary changes not only regarding foundations and ownership structure of nursery care institutions, but also in a sphere of legislative and subsidy activity of municipal self-governments. On the basis of the new law municipal councils obtained a statutory delegation to determine, by means of an act of a local law, an amount and rules for determining and accounting for a special-purpose subsidy granted from the municipal budget to entities running a nursery or a children’s club, day carers or persons employing day carers. This sphere of self-government subsidies reveals an extraordinary “ingenuity” of municipal councils in determining the above principles. That “ingenuity” quite often meets a supervisory reaction of a regional chamber of audit. The aim of the article is to justify the research thesis that granting a nursery subsidy from a commune’s budget exemplifies its broadest subsidy’s independence in a field of legislative and expenditure activity of a commune’s authorities. In order to prove the above thesis, the conducted research included a comparative analysis of the nursery subsidy with other subsidies granted from budgets of local government units (in particular with an educational subsidy), as well as an analysis of supervisory and judicial decisions regarding resolutions of municipal councils adopted on the basis of the authorization under Article 60(2) of the above Act. In order to illustrate an expenditure activity of a commune in this respect a quantitative method was also used by presenting an analysis of a budget expenditure of one of a voivodship cities on nursery subsidies. Assuming that in a city with a poviat status, which is also a capital of a voivodeship all forms of care for children up to 3 years of age should function, the article analyzes the budget expenditure of such a city on nursery care. This analysis showed the size and structure of the nursery subsidies granted by the above city, which in turn confirmed the existence of the commune’s independence in this respect. The results of the analyzes carried out in the article were also related to the issues of granting nursery subsidies in periods of the pandemic crisis and the refugee crisis.